The prevalence of enamel hypoplasia on permanent teeth among children aged 9-12 years based on the type and teeth affected - Sari, Desy Permata; Primarti, Risti Saptarini; Herdiyati, Yetty (Padjadjaran Journal of Dentistry, 2010)
Introduction: Enamel hypoplasia is defect which is an abnormality on the enamel structure. The abnormality causes an aesthetic problems that affects the psycologic of a child, and also makes it easier to form a caries. The purpose of this research was to find the prevalence of enamel hypoplasia on permanent teeth among children ages 9-12 years based on the type and teeth that are affected. Methods: The research was descriptive with survey technique. The samples were taken by purposive sampling technique, which were 96 children. The research were done to erupted permanent teeth. location of research is in dental hospital faculty of dentistry Universitas Padjadajran. Results: The result of this research shows that seven children (7.29%) has enamel hypoplasia on their permanent teeth, the amount of teeth that are affected are 15. Enamel hypoplasia has occurred to one child (1.04%) ages nine, three children (3.13%) ages ten, one child (1.04%) ages 11, and two children (2.08%) ages 12. Conclusion: Prevalence of enamel hypoplasia on permanent teeth among children ages 9-12 years UNPAD was 7.29%. Enamel hypoplasia occurred to 15 teeth, which are six of them (40%) was type III. The most common teeth that are affected is premolar, which are eight teeth (53.33%).